2022
DOI: 10.1111/imm.13607
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 activation is required for cytotoxic response elicited by baculovirus capsid display

Abstract: Although the baculovirus Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) infects lepidopteran invertebrates as natural hosts, represents an efficient vector for vaccine development. Baculovirus surface display induces strong humoral responses against viruses and parasites. A novel strategy based on capsid display carrying foreign antigens in the AcMNPV particle further improved the immune response by eliciting CD8+ T cell activation. In this study, we analyze the intracellular mechanisms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Molinari et al. revealed that Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) carrying a fragment of OVA (chicken egg ovalbumin) fused to the N terminus of VP39 protein (BV-cOVA) triggers endosomal TLR9 signaling in DCs, which triggers a CD8 + T cell-mediated adaptive immune response through the TLR9/MyD88 pathway ( 80 ). We identified that STM2457 treatment in the cocultured cell systems can inhibit the expression levels of CD107a + and IFN-γ + in CD8 + T and CD4 + T cells upon CpG-ODN stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Molinari et al. revealed that Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) carrying a fragment of OVA (chicken egg ovalbumin) fused to the N terminus of VP39 protein (BV-cOVA) triggers endosomal TLR9 signaling in DCs, which triggers a CD8 + T cell-mediated adaptive immune response through the TLR9/MyD88 pathway ( 80 ). We identified that STM2457 treatment in the cocultured cell systems can inhibit the expression levels of CD107a + and IFN-γ + in CD8 + T and CD4 + T cells upon CpG-ODN stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of the antigen at the capsid or envelope surface of recombinant BV is crucial because differential immune responses are triggered (Tavarone et al, 2017). In particular, we have previously demonstrated that the expression and presentation of a model antigen at the BV capsid promotes strong cellular responses, along with a specific IFNɣ production by cytotoxic CD8+ lymphocytes (Molinari et al, 2011(Molinari et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have previously demonstrated that the expression and presentation of a model antigen at the BV capsid promotes strong cellular responses, along with a specific IFNɣ production by cytotoxic CD8+ lymphocytes 25,26 .…”
Section: Introductionmentioning
confidence: 99%